UPAYA PENGEMBANGAN KOMPETENSI GURU SMK DI DAERAH KHUSUS IBUKOTA JAKARTA DALAM PEMANFAATAN INFORMATION AND COMMUNICATION TECHNOLOGY MELALUI PELATIHAN PERANCANGAN WEBSITE BERBASIS WORDPRESS - Erdawaty; Avianti, Ratu Amilia (LPPM Universitas Negeri Jakarta, 2021)
Teachers are the spearhead that can shape the character and spirit of the Indonesian nation, both the good and bad of the nation is very dependent on the teacher. How great is the role of the teacher, so that teachers are needed who are professional, creative, innovative, have a high willingness to continue learning, and are literate in information technology, so they are able to keep abreast of the times. Website is an internet facility that can display information interactively. Through the website, users can exchange information so they can follow the development of science and technology quickly. Website provide many benefits if used wisely. However, in reality there are still many teachers who have not been able to increase their professional potential in developing websites. For this reason, a WordPress-based website design training program was designed for teachers of SMK Negeri 26 Jakarta. This training uses the